Driving mechanism of suspended minerals on the multi-level bioavailability of citalopram in Daphnia magna - Haohan Yang; Hanyu Jiang; Hao Xing; Zhankun Chen; Qi Zhang; Zhenhua Yan (Journal of Environmental Sciences, 2026)

Smart spherical tracking probe for visualizing soil flow in cutter chamber of shield tunneling machine - Xiaokelaiti Kudereti; Xiaoyong Kou; Haohan Yang; Miao Fu; Shaokong Feng; Guanlin Ye (Tunnelling and Underground Space Technology, 2026)

Climate-driven drainage reorganization and fluvial incision in the Huangshui River Basin, northeastern Tibetan Plateau - Qiang Su; Xianyan Wang; Yang Yu; Dongxu Cai; Zhengchen Li; Haohan Wu; Huayu Lu (Geomorphology, 2026)

Secondary interfacial polymerization seals defects to repurpose water treatment thin film composites membranes for CO2 capture - YiKai Wang; Zixue Zhao; Long Shi; Tianyi Zhou; Haohan Wan; Gang Zhang; Chuanrong Liu; Wenju Jiang; Lin Yang; Lu Yao; Junfeng Zheng; Zhongde Dai; et al. (Chemical Engineering Journal, 2026)

Research on solubility prediction method for milk powder quality assessment: based on morphological characteristics - Haohan Ding; Yinghao Yang; Xiaodong Song; Guanjun Dong; Xiaohui Cui; Xueru Zhang; Wei Yu; David I. Wilsone (Food Chemistry, 2026)

Advances on Sporisorium reilianum: microbiology along with chemistry, bioactivity, and application - Yihua Wang; Yansong Meng; Zezhuang Hao; Haohan Yang; Zhixin Shen; Denghui Yu; Ye Wang; Shuguang Guan; Yuling Ding; Yong Li (Folia Microbiologica, 2026)

A federated learning-based Aflatoxin M1 prediction model under a data enhancement strategy - Long Wang; Xiaodong Song; Haohan Ding; Xiaohui Cui; David I. Wilson; Wei Yu; Yinghao Yang; Guanjun Dong (Journal of Food Engineering, 2026)

Pathogen biosensors for food safety and public healthcare based on specific biological probes biopanned by phage display: A critical review - Mingyang Wang; Zhonghuang Yang; Xin Liu; Yuxuan Jiang; Haohan Zhang; Aihua Liu (Food Chemistry, 2025)

Migrating incision wave and the bottom-up drainage integration of the upper Yangtze River on the Tibetan Plateau before Pliocene times - Yang Yu; Xianyan Wang; Zhengchen Li; Qiang Su; Dongxu Cai; Haohan Wu; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Transport mechanisms and fate of neonicotinoids in the soil-water systems under the effects of wetting-drying cycles and rice cultivation - Shu Ji; Haomiao Cheng; Tengyi Zhu; Hanyang Xu; Guanlong Tang; Jian Zhang; Fukan Yang; Haohan Yang (Environmental Pollution, 2025)

Effect of functional groups of polystyrene nanoplastics on the neurodevelopmental toxicity of acrylamide in the early life stage of zebrafish - Haohan Yang; Linghui Kong; Zhuoyu Chen; Jun Wu (Aquatic Toxicology, 2025)

A facile solvent activation process manipulates the structure and filtration performance of oxidized poly (arylene sulfide sulfone) TFC membrane - Haohan Wan; Xinyi Yan; Jie Yang; Guangming Yan; Gang Zhang (Desalination, 2024)

Isolation and characterization of DPP-IV inhibitory peptide from rabbit meat hydrolysate: Mechanism, gastrointestinal resistance, and hypoglycemic effects of Leucyl-Leucine (LL) - Haohan Hu; Jianfei Li; Feng Chen; Chenying Yang; Yuexin Pan; Wanzhou Yang; Xiaodong Yu; Qiyi He (Food Bioscience, 2024)

Occurrence, source apportionment and risk assessment of selected pharmaceuticals and their transformation products in the effluent-impacted rivers - Sisi Liu; Haohan Yang; Zhipeng Wang; Jun Wu; Zhigang Liu; Hui Mao; Zhengxie Zhou; Binni Ma; Xueyu Wei; Qingbo Shang (Regional Studies in Marine Science, 2024)

Integrated assessment of the pollution and risk of heavy metals in soils near chemical industry parks along the middle Yangtze River - Dong Xu; Zejun Wang; Xiaoyu Tan; Haohan Xu; Dongbo Zhu; Ruili Shen; Kang Ding; Hongcheng Li; Luojing Xiang; Zhibing Yang (Science of The Total Environment, 2024)

Single-stage partial nitrification/anammox process performance restoration by bio-augmenting nitrifiers with or without nitrite oxidizing bacteria suppression - Chi Zhang; Miao Zhang; Haohan Yang; Wei Cai; Jun Wu (Journal of Water Process Engineering, 2024)

Acute toxicity of tire wear particles and leachate to Daphnia magna - Jiaqiang Liu; Qiyan Feng; Haohan Yang; Xiulei Fan; Yuanyuan Jiang; Tao Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Effects of differential regional PM2.5 induced hepatic steatosis and underlying mechanism - Zhipeng Yan; Shuyue Li; Rui Chen; Haohan Xie; Meiqiong Wu; Nan Nan; Qisong Xing; Yang Yun; Guohua Qin; Nan Sang (Environmental Pollution, 2023)

Tissue-specific accumulation, depuration, and effects of perfluorooctanoic acid on fish: Influences of aqueous pH and sex - Huike Dong; Guanghua Lu; Xiaoping Wang; Peng Zhang; Haohan Yang; Zhenhua Yan; Jianchao Liu; Runren Jiang (Science of The Total Environment, 2023)

Developing a UV dosing strategy for UV/chlorine process towards the trade-off between pharmaceuticals and personal care products degradation and disinfection by-products formation - Shi Cheng; Yanting Zuo; Aimin Li; Haohan Jiang; Wenliang Ji; Ji Wu; Wentao Li; Zhe Wang; Yonglin Zhou; Feng Zhu; Wei He; Zongli Huo; et al. (Journal of Cleaner Production, 2023)

Interactive neurotoxicity of environmentally relevant concentrations of polystyrene nanoplastics and butyl methoxydibenzoyl methane on early zebrafish embryos - Ranran Zhou; Haohan Yang; Dao Zhou; Shixin Yang; Zhiqiao Shi; Qijie Jin; Zhuhong Ding (Frontiers in Marine Science, 2022)
Organic ultraviolet filters (OUVFs) and nanoplastics (NPs) are two important new pollutants that coexist widely in freshwater and coastal habitats. Both OUVFs and MPs can be taken up by aquatic organisms and may be toxic or co-toxic. In this study, the neurotoxicity and interaction neurotoxicity of the typical OUVFs butyl methoxydibenzoyl methane (BM-DBM) and polystyrene nanoplastics (PS-NPs) on zebrafish at environmental concentrations were comprehensively investigated at the tissue and molecular levels using transgenic or non-transgenic zebrafish. Results showed that both BM-DBM and PS-NPs induced abnormal expression of developmental genes neurogenin 1 , glial fibrillary acidic protein , Finkel-Biskis-Jinkins osteosarcoma oncogene , growth-associated protein 43 , synapsin IIa , and apoptosis regulator a ( Bcl2a ), Bcl2 associated x and apoptosis-related cysteine peptidase a , neuronal loss, motor neuron axon deletion, neuronal apoptosis and behavioral abnormalities in larvae thus being neurotoxic. BM-DBM also specifically interferes with neurotransmitter systems and affects signaling between neurons. In addition, PS-NPs and BM-BDM exerted synergistic and antagonistic effects in inducing apoptosis in neuronal cells and developmental neurotoxicity, respectively. Our results highlight the neurotoxic risk of PS-NPs and BM-BDM and the complex interactive neurotoxic effects of the two. We anticipate that our study may lay the foundation for ecological risk assessment of OUVFs and PS-NPs and exploration of complex interactions between PS-NPs and hydrophobic organic pollutants.

Bioconcentration, behavioral, and biochemical effects of the non-steroidal anti-inflammatory drug diclofenac in Daphnia magna - Matthew Nkoom; Guanghua Lu; Jianchao Liu; Huike Dong; Haohan Yang (Environmental Science and Pollution Research, 2019)

Bioconcentration and effects of hexabromocyclododecane exposure in crucian carp (Carassius auratus) - Huike Dong; Guanghua Lu; Zhenhua Yan; Jianchao Liu; Haohan Yang; Matthew Nkoom (Ecotoxicology, 2018)

The effects of dissolved organic matter and feeding on bioconcentration and oxidative stress of ethylhexyl dimethyl p-aminobenzoate (OD-PABA) to crucian carp (Carassius auratus) - Binni Ma; Guanghua Lu; Haohan Yang; Jianchao Liu; Zhenhua Yan; Matthew Nkoom (Environmental Science and Pollution Research, 2018)

Biological effects of citalopram in a suspended sediment-water system on Daphnia magna - Haohan Yang; Guanghua Lu; Zhenhua Yan; Jianchao Liu; Binni Ma; Huike Dong (Environmental Science and Pollution Research, 2017)

Toxicity of Cu and Cr Nanoparticles to Daphnia magna - Guanghua Lu; Haohan Yang; Jun Xia; Yongchen Zong; Jianchao Liu (Water, Air, & Soil Pollution, 2017)

The effects of endoplasmic reticulum stress response on duck decorin stimulate myotube hypertrophy in myoblasts - Lingli Sun; Kai Lu; Hehe Liu; Haohan Wang; Xinxin Li; Chao Yang; Liang Li; Jiwen Wang (Molecular and Cellular Biochemistry, 2013)